خواجہ محمد قمر الدین سیا لوی کی علمی و ادبی خدمات: Khwāja Qamar-ud-Dīn Siālviī’s Scholarly and Literary services (Al-Qamar, 2020)
This article studies the scholarly and literary services of Khwāja Qamar-ud-Dīn Siālviī’s (1906-1981), a great religious scholar, Sufi, poet and politician from Siāl Sharīf, Punjab, Pakistan. It finds that saints of Siāl Sharīf particularly Khwāja Qamar-ud-Dīn Siālviī has made practical efforts to reform the beliefs of Pakistani society, the supremacy of the Quran and Sunnah, the preservation of the doctrine of the finality of the Prophet and the restoration of the Constitution of Pakistan. Highlighting the scholarly and literary achievements of the great sheikh and his caliphs is the need of the hour to draw guidance from the writings of this great Sufi poet and scholar to eradicate the growing conspiracies and fabrications against the religion of Islam in modern times. If we look at the evolution of Urdu mystical literature, the works of art created in monasteries are still popular. From Amīr Khosrow (1253-1325 AD) to the present moment, writers of Chishī Sufi order have made extraordinary efforts for the genres of Ḥamd, Na‘t, Manqibat and Salām. The study maintains that Siālvī took active part in the Pakistan Movement and devoted his life for the establishment of Nizām-i-Mustafā. He has done remarkable works in the field of literature as well.
Keywords: Khwāja Qamar-ud-Dīn Siālviī; services; scholarly; literary